Outcomes after arthroscopic revision surgery for anterior cruciate ligament injuries - Yumashev, Alexei V; Baltina, Tatyana V; Babaskin, Dmitrii V (Acta Orthopaedica, 2021)
Background and purpose — The frequency of primary anterior cruciate ligament (ACL) reconstruction is increasing resulting in more ACL revision surgeries. Therefore, we assessed survival rates of 2 different grafts for ACL revision surgery at 1- and 5-year follow-ups, as well as physical activity levels of patients after revision surgery. Patients and methods — This is a retrospective cohort study involving 218 patients (176 males) who had revision surgery for anterior cruciate ligament injuries between 2008 and 2017 at the Clinic of Traumatology, Orthopedics and Joint Pathology Clinic (I.M. Sechenov First Moscow State Medical University). A comparison group involved 189 patients with only primary surgery. Surgical interventions were performed according to the standard procedure using bone–patellar tendon–bone (BTB) and semitendinosus/gracilis (ST/G) autografts. The results of revision surgery were assessed at 1- and 5-year follow-ups by using the Lysholm and International Knee Documentation Committee scores. Results — Malpositioned bone tunnels were found in 87/218 patients (40%). At 1 and 5 years postoperatively, the revision BTB group had significantly better results in terms of IKDC and Lysholm scores than the revision ST/G group (p = 0.03, Mann–Whitney U-test), and these results were comparable to those in the comparison group. Graft survival after revision was lower than after the primary operation. However, the survival rate of 80% is quite high and is consistent with previous findings. There were no statistically reliable differences in survival between ST/G and BTB autografts. Interpretation — The graft choice for revision ACL surgery should be decided upon before surgery based on, among other things, the state of bone tunnels, in particular their position and degree of bone resorption. Tunnel widening that exceeds 14 mm (osteolysis) would require 2-stage surgery using a BTB autograft with bone plugs because it is larger than the ST/G autograft.